Project Approach as a Means of Forming the Availability of Bachelors to Innovate Activity in Information Technologies - Akhmetzyanova, Guliya; Pronina, Zinaida; Bagateeva, Angelina (Journal of History Culture and Art Research, 2018)
The article presents the author’s interpretation of the structure of availability of bachelors for innovative activity in the field of information technology, reveals the essence of the project approach in its formation. Information technologies have a number of features that affect the innovation policy: the dynamics of the industry; the novelty of the products and services offered, the rapid growth of the information service market; the use of advanced technologies in the field of information technology. One of the main objectives of the educational system in the field of information technology is to ensure the forming of students’ special competencies of innovative activity with the help of various modern pedagogical approaches. Thus, the development of methodical, didactic bases of the organization of project activity in the field of information technologies acquires special urgency.